Digital transformation and organizational innovation: challenges, opportunities, and perspectives for business competitiveness - Pardo, Germán Pablo (Revista JRG de Estudos Acadêmicos, 2025)
This article examines digital transformation and its influence on organizational innovation, highlighting how the integration of digital technologies has reshaped business models, internal processes, and competitive strategies within companies. The analysis addresses the main challenges organizations face when implementing digital initiatives, as well as the opportunities created to foster continuous innovation. The study also emphasizes the crucial role of organizational culture, adaptive capacity, and strategic leadership as critical success factors in this transformational process. Finally, the article discusses future perspectives and presents practical recommendations for organizations seeking to remain relevant and competitive in the digital age.